Sibling Rivalry and Psychological Well-Being in Early Adulthood - Livia Umar; Setiawati Intan Savitri (Universitas Mercu Buana Jakarta, 2026)
Many cases of sibling rivalry, including crimes, are committed by young adults who are usually considered independent, responsible and have good psychological well-being. These cases are caused by parental injustice. Parenting patterns that create sibling rivalry. This study aims to determine whether there is a significant relationship between sibling rivalry and psychological well-being in early adults in Jakarta. The research method used is quantitative with the criteria for male or female, aged 18-29, having at least one sibling and domiciled in Jakarta. Sibling rivalry was measured using the ASRQ Rivalry Subscale (Stocker, 1997), adapted via expert judgment, while psychological well-being used the SPWB (Ryff & Keyes) adapted by Fadhil (2021). The 114 respondents were obtained and analyzed using SPSS and Spearman's rho correlation test. The results showed no significant relationship between sibling rivalry and psychological well-being. This means that higher levels of sibling rivalry do not necessarily increase or decrease psychological well-being, and vice versa. However, in the correlation matrix, sibling rivalry correlated positively with the Positive Relations with Others dimension and negatively with the Personal Growth dimension.